Time is now to consider how we evaluate person-centred care—the role of patient-reported outcomes - Claudia Rutherford; Claudia Rutherford; Jan Boehnke; Joanne Greenhalgh; Vaibhav Tyagi; Tanya McCance; Brendan McCormack (Frontiers in Health Services)
Person-centred care refers to health care that is respectful of and responsive to personal experiences, preferences, needs, goals and values of service users. Despite the growing recognition of the value of patient-reported outcome measures, they are rarely used as evaluation endpoints in person-centred care research and care practices. This paper contributes to knowledge by examining the opportunities and challenges of using patient-reported outcome measures to measure person-centred care. Our focus is not the collection and feedback of patient-reported outcomes to enact person-centred care. We discuss differences between patient- and person-reported outcomes and their role in assessing person-centred care. We also challenge some existing measurement practices and usage of existing patient-reported outcome measures. We critically discuss some potential consequences of current practices, and present possible solutions. We do not have all the answers, and we urge those working in the field of patient-reported measurement to collectively come together to find solutions. With this perspective article, we aim to start the conversation to think differently about how we evaluate person-centred care and propose areas of enquiry that incorporate patient-reported outcomes into the evaluation of person-centred care.